Video Resumes and Job Search Outcomes: Evidence from a Field Experiment - Charles Bellemare; Marion Goussé; Guy Lacroix; Steeve Marchand (Institute of Labor Economics (IZA), 2020)
We evaluate the efficiency of video resumes using a large scale field experiment. We randomly sent applications to 2021 private firms posting vacancies across the province of Québec (Canada). A subset of these applications included a link inviting firms to view a video resume. We find that video resumes increase callback rates by more than 10 percentage points. We also evaluate the service for individuals with acute visible disabilities (wheelchair users). Although our results support the presence of discrimination in the labor market, we show that they benefit from video resumes as much as applicants without a disability.
Keywords: J71; J68; 330; video resume; job search; disabilities; discrimination